2011
DOI: 10.1002/cpa.20383
|View full text |Cite
|
Sign up to set email alerts
|

Rough stochastic PDEs

Abstract: In this article, we show how the theory of rough paths can be used to provide a notion of solution to a class of nonlinear stochastic PDEs of Burgers type that exhibit too-high spatial roughness for classical analytical methods to apply. In fact, the class of SPDEs that we consider is genuinely ill-posed in the sense that different approximations to the nonlinearity may converge to different limits. Using rough path theory, a pathwise notion of solution to these SPDEs is formulated, and we show that this yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 33 publications
1
112
0
Order By: Relevance
“…It is then possible to simply "postulate" the values of the integrals X s,t =: satisfying "Chen's relations" X s,t − X s,u − X u,t = X s,u ⊗ X u,t , (1.4) as well as the analytic bound |X s,t | |t − s| 2α , and to exploit this additional data to give a coherent definition of expressions of the type Y dX, provided that the path X is "enhanced" with its iterated integrals X and Y is a "controlled path" of the type (1.2). See for example [Gub04] for more information or [Hai11] for a concise exposition of this theory.…”
Section: Remark 12mentioning
confidence: 99%
“…It is then possible to simply "postulate" the values of the integrals X s,t =: satisfying "Chen's relations" X s,t − X s,u − X u,t = X s,u ⊗ X u,t , (1.4) as well as the analytic bound |X s,t | |t − s| 2α , and to exploit this additional data to give a coherent definition of expressions of the type Y dX, provided that the path X is "enhanced" with its iterated integrals X and Y is a "controlled path" of the type (1.2). See for example [Gub04] for more information or [Hai11] for a concise exposition of this theory.…”
Section: Remark 12mentioning
confidence: 99%
“…The argument is essentially the same as the one given in [Hai11], which in turn relies very heavily on the results in [FV10a,FV10b], so we only explain the main steps and refer to [Hai11] for more details.…”
Section: Construction Of the Area Processmentioning
confidence: 99%
“…Special thanks are due to Hendrik Weber for numerous suggestions and his careful reading of the draft manuscript, as well as to Gérard Ben Arous who suggested that the techniques developed in [Hai12,Hai11] might prove useful for analysing the KPZ equation.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations